Amaranthus caudatus L. as a source of betacyanins with coloring and antimicrobial properties. - Roriz, Custódio Lobo (2018)
Amaranthus caudatus L. is a plant belonging to the Amaranthaceae family, and is a very interesting crop, since it resists drought, heat, and pests, and adapts readily to new environments. The visual appearance of this plant is a bright red-violet, being betacyanins the compounds responsible for the color, and several bioactivities. Therefore, and despite being considered a good source of nutrients with high quality proteins, vitamins, minerals and bioactive molecules, such as phenolic compounds, A. caudatus can also be commercially exploited as a source of natural colorants. In the last decade, and due to the growing demand of consumers, natural matrices have been used to search natural colorant alternatives, in order to replace the artificial counterparts, which have been revealed some toxic effects. Betacyanins are natural colorants and have been used in the food industry, not only because of the high colouring power, but also due to recognized bioactive properties, such as antioxidant and antimicrobial, among others. Thus, the objective of this work was to obtain an extract rich in betacyanins to be used as food coloring agents, offering an alternative source of these coloring compounds, but at the same time conferring bioactive properties. A dynamic maceration extraction was carried out, being the extracts characterized by HPLC-DAD-ESI/MS regarding betacyanins’ composition. The antibacterial activity was evaluated against a panel of four Gram-positive and five Gram-negative bacteria, and the absence of cytotoxicity was confirmed in a porcine liver primary culture. By the chromatographic analysis it was possible to identify four compounds, being amaranthine (171 ± 1 mg/g extract) and isomaranthine (38 ± 1 mg/g) the two major compounds, and betanin (1.6 ± 0.1 mg/g) and isobetanin (1.3 ± 0.1 mg/g) the minor compounds. The extract presented minimum growth inhibitory concentrations (MICs) ranging from 20-10 mg/mL, with no cytotoxicity. After such promising results, this plant can be a viable alternative to obtain natural colorant ingredients.